Mulheres à deriva : deslocamentos e filiações em Carola Saavedra e Jean Rhys - Duarte, Giovanna de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
O presente trabalho analisa a partir de uma perspectiva crítica comparatista, a construção das protagonistas femininas dos romances Com armas sonolentas (2018), da brasileira Carola Saavedra, e Voyage in the dark (1934), da autora dominicana Jean Rhys. A análise comparativa das personagens objetiva a aproximação dessas a partir das experiências que compartilham entre si, relacionadas à memória familiar e ao exílio, considerando os deslocamentos geográficos, identitários e culturais que caracterizam tais experiências. Ademais, analisamos os processos de rememoração como mecanismos de superação traumática e de (re)construção de si, dentro e fora das narrativas, examinando aspectos autoficcionais e as possíveis relações das obras com o gênero denominado romance de filiação. A base teórica do presente trabalho é constituída por María Lugones (2008), Gloria Anzaldúa (1981), Edward Said (2003), Susan Friedman (2004), Elisabeth Badinter (1985), Zila Bernd (2018), Anna Faedrich (2015), Eurídice Figueiredo (2013), Adrienne Rich (1981), Heloisa Buarque de Holanda (1994), dentre outros.

This paper aims to analyze, from a critical comparative perspective, the construction of the female protagonists in the novels Com armas sonolentas (2018) by Brazilian author Carola Saavedra and Voyage in the dark (1934) by Dominican author Jean Rhys. The comparative analysis of the characters aims to bring them closer together based on the experiences they share with each other, related to family memory and exile, considering the geographical, identity and cultural displacements that characterize these experiences. In addition, we analyze the processes of remembrance as mechanisms for overcoming trauma and (re)constructing the self, both inside and outside the narratives, examining autofictional aspects and the possible relationship between the works and the genre known as the novel of filiation. The theoretical basis of this work is made up of María Lugones (2008), Gloria Anzaldúa (1981), Edward Said (2003), Susan Friedman (2004), Elisabeth Badinter (1985), Zila Bernd (2018), Anna Faedrich (2015), Eurídice Figueiredo (2013), Adrienne Rich (1981), Heloisa Buarque de Holanda (1994), among others.
Women adrift : displacements and affiliations in Carola Saavedra and Jean Rhys
Keywords: Literatura comparada; Memória; Exílio; Saavedra, Carola, 1973-; Rhys, Jean; Comparative Literature; Memory; Exile